Investigation of Low-Temperature Behavior of Stone Mastic Asphalt Mixtures Modified with Paraffin and Crumb Rubber - Kök, Baha Vural; Yılmaz, Mehmet; Akpolat, Mustafa (My University, 2017)
In hot mix asphalts at low temperatures, cracks occur due to thermal tension and these cracks cause water to leak inside the pavement and the pavement gets deformed sooner than expected. In order to improve the properties of bituminous mixtures, mostly polymer type additives are used in the modification of the bitumen. These types of improvements usually have positive effects on the high-temperature behavior of the mixture. In this study, semi-circular bending test, which is the most commonly used method in the literature to investigate the low-temperature behavior of bituminous mixtures, was performed. In the study, the resistance of stone mastic asphalt mixtures, which were prepared with modified bitumen with a constant 3% of paraffin and various amounts of crumb rubber, to crack formation and its movement was identified. As a result, it was concluded that the effects of additives on crack formation and its movement is varied and the relation between the fractured aggregate surface areas and the fracture toughness of the mixture can be determined by the image processing method.
Keywords: İnşaat Mühendisliği